A Review of the Impact of Capability Illusions Induced by Generative Artificial Intelligence on Individual Investors' Overconfidence: From the Perspective of Heterogeneity in Investment Decision Efficiency and Risk Preferences - Zhu, Hankun (Exploring Science Academic Conference Series, 2026)
With the rapid commercialisation of Generative Artificial Intelligence (GenAI) in the field of financial investment, the illusion and overconfidence of individual investors' skills have become an important factor affecting the efficiency of investment decision-making. This review brings together the research published by Web of Science, Google Scholar and CNKI from 2020 to 2026. It is found that GenAI greatly increases the skill fantasy of retail investors, which makes their overconfidence stronger. The efficiency of investment decision-making is a bit like a bridge in this relationship, and the difference of risk preference is an important variable, which changes the intensity of this effect among different investor groups. This paper summarises the researchers' thoughts today, shows the differences and unknown contents, and puts forward ideas for future research. The purpose of this review is to provide theoretical reference for the interdisciplinary study of GenAI and investor behaviour. It also provides some practical suggestions, which could help individual investors avoid misjudgement and help financial institutions improve their services based on artificial intelligence.